Alkyl substituted aminal derivatives of HCV NS5A inhibitor MK-8742. Issue 15 (1st August 2016) - Yu, Wensheng; Coburn, Craig A.; Nair, Anilkumar G.; Wong, Michael; Tong, Ling; Dwyer, Michael P.; Hu, Bin; Zhong, Bin; Hao, Jinglai; Yang, De-Yi; Selyutin, Oleg; Jiang, Yueheng; et al.
Graphical abstract: Abstract: HCV NS5A inhibitors have demonstrated impressive in vitro potency profiles in HCV replicon assays and robust HCV RNA titer reduction in the clinic making them attractive components for inclusion in an all oral fixed dose combination regimen for the treatment of HCV infection. Herein we describe our continued research efforts around the alkyl "Z group" modification of the tetracyclic indole-based NS5A inhibitor MK-8742, which led to the discovery of a series of potent NS5A inhibitors. Compounds10 and19 are of particular interests since they are as potent as our previous leads and have much improved rat pharmacokinetic profiles.